Separation of non-stationary multi-source sound field based on the interpolated time-domain equivalent source method. (May 2016) - Bi, Chuan-Xing; Geng, Lin; Zhang, Xiao-Zheng
Abstract: In the sound field with multiple non-stationary sources, the measured pressure is the sum of the pressures generated by all sources, and thus cannot be used directly for studying the vibration and sound radiation characteristics of every source alone. This paper proposes a separation model based on the interpolated time-domain equivalent source method (ITDESM) to separate the pressure field belonging to every source from the non-stationary multi-source sound field. In the proposed method, ITDESM is first extended to establish the relationship between the mixed time-dependent pressure and all the equivalent sources distributed on every source with known location and geometry information, and all the equivalent source strengths at each time step are solved by an iterative solving process; then, the corresponding equivalent source strengths of one interested source are used to calculate the pressure field generated by that source alone. Numerical simulation of two baffled circular pistons demonstrates that the proposed method can be effective in separating the non-stationary pressure generated by every source alone in both time and space domains. An experiment with two speakers in a semi-anechoic chamber further evidences the effectiveness of the proposed method. Highlights: A separation model of non-stationary multi-source sound field is proposed. The interpolated time-domain equivalent source method is applied to the separation. Numerical and experimental results prove the effectiveness of the proposed method.